The Influence of Leadership and Organizational Culture on Nurses' Performance Through Motivation as an Intervening Variable - Suartiningsih, I Gusti Ayu Suartiningsih; Ni Luh Sili Antari; Santika, I Putu Santika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This research aims to analyze the influence of leadership and organizational culture on nurses' performance through motivation as an intervening variable at Surya Husadha General Hospital in Denpasar. The population of this research consists of all nurses at Surya Husadha General Hospital in Denpasar. Samples were taken from each unit using disproportional random sampling technique with a total of 69 samples. The research analysis technique was conducted using a path analysis approach, where the data has been tested for validity, reliability, and classical assumption testing. The results of the analysis show that leadership has a positive and significant influence on motivation; organizational culture has a positive and significant influence on motivation; leadership has a positive and significant influence on nurses' performance; motivation has a positive and significant influence on nurses' performance; and motivation cannot mediate leadership's influence on nurses' performance. This research hopes to improve leadership, organizational culture, motivation, and nurses' performance. Keywords: leadership, organizational culture, motivation, performance